2000
DOI: 10.1107/s1600536800018110
|View full text |Cite
|
Sign up to set email alerts
|

A linear supramolecular array of {[Mn(H2O)2(15-crown-5)]Br2}n

Abstract: Di­aqua(1,4,7,10,14‐penta­oxa­cyclo­penta­decane)­manganese(II) dibromide, [Mn(C10H20O5)(H2O)2]Br2, prepared in a search for emissive MnII ions in unusual coordination environments, contains the metal ion encircled by the crown ether ligand, with the water mol­ecules in trans axial positions. Hydro­gen bonding between these and the Br− counter‐ions forms chains of cations running approximately parallel to a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Reid et al reported the crystal of [Mn 2z (H 2 O) 2 (15-crown-5)]Br 2 , in which [Mn 2z (H 2 O) 2 (15crown-5)] units are connected by H … Br bonds and they form an infinite columnar structure. 7 In the present crystal, the nitrogen atoms of CH 3 CN interact with the K z , and each SC z (supramolecular cation) unit associates with an adjacent SC z unit through the CH 3 CN-CH 3 CN dipole-dipole interaction. In each column, V-shaped SC z units are aligned in the same direction along the b-axis one-dimensionally with the two benzene rings towards the a-axis.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Reid et al reported the crystal of [Mn 2z (H 2 O) 2 (15-crown-5)]Br 2 , in which [Mn 2z (H 2 O) 2 (15crown-5)] units are connected by H … Br bonds and they form an infinite columnar structure. 7 In the present crystal, the nitrogen atoms of CH 3 CN interact with the K z , and each SC z (supramolecular cation) unit associates with an adjacent SC z unit through the CH 3 CN-CH 3 CN dipole-dipole interaction. In each column, V-shaped SC z units are aligned in the same direction along the b-axis one-dimensionally with the two benzene rings towards the a-axis.…”
Section: Resultsmentioning
confidence: 72%
“…4 Weak interactions such as hydrogen bonding and p-p interactions are utilized to construct infinite columns and chiral double-helices, which are important models in biological systems. [5][6][7][8] The cation structure largely affects [Ni(dmit) 2 ] 2 arrangements within the crystals. We introduced supramolecular cation structures composed of inorganic metal cations-crown ethers as a counter cation for [Ni(dmit) 2 ] 2 anionic species.…”
Section: Introductionmentioning
confidence: 99%